Sol-gel synthesis, optical properties, morphology and photocatalytic activity of titania films modified with ethanolamines as nitrogen source - Linnik, O.P.; Shestopal, N.O.; Smirnova, N.P.; Eremenko, A.М.; Stanculescu, A.; Socol, M. (Поверхность, 2012)
In this work the titania films modified with ethanolamines are synthesized by sol-gel method using two different routes. Introduction of template during sol ripening leading to the formation of porous structure and a single stage synthesis resulting in non-porous surface are proposed. The optical properties and calculated band-gap values of the films are presented. The titania particle size of the modified films is increased in comparison with the bare one as results of Root mean square (RMS) and Roughness average (Ra) values. The influence of the synthesis conditions and structure of ethanolamines on the photocatalytic activity under visible light are reported. В данной работе синтезированы пленки диоксида титана, модифицированные этаноламинами. Описан золь-гель метод с использованием различных. Введение темплата во время созревания золя приводит к образованию пористой структуры, а предложенный одностадийный синтез формирует непористую поверхность. Исследованы оптические свойства пленок и рассчитаны их величины ширины запрещенной зоны. Размер частиц модифицированных пленок диоксида титана возрастает по сравнению с немодифицированным, как показано представленными значениями RMS и Ra. Изучено влияние условий синтеза и структуры этаноламинов на фотокаталитическую активность под видимым светом. Синтезовано плівки діоксиду титану, модифіковані етаноламінами. Описано золь-гель метод з використанням різних підходів. Введення темплату під час дозрівання золю призводить до утворення пористої структури, а запропонований одностадійний синтез формує непористу поверхню. Досліджено оптичні властивості плівок та розраховано їхні величини ширини забороненої зони. Розмір частинок модифікованих плівок діоксиду титану зростає в порівнянні з немодифікованим, як показано представленими значеннями RMS і Ra. Вивчено вплив умов синтезу і структури етаноламінів на фотокаталітичну активність під видимим світлом.